Long noncoding RNA LINC01606 protects colon cancer cells from ferroptotic cell death and promotes stemness by SCD1–Wnt/β‐catenin–TFE3 feedback loop signalling. Issue 4 (29th April 2022) - Luo, Yajun; Huang, Siqi; Wei, Jinlai; Zhou, He; Wang, Wuyi; Yang, Jianguo; Deng, Qican; Wang, Hao; Fu, Zhongxue
Abstract: Background: Ferroptosis is principally caused by iron catalytic activity and intracellular lipid peroxidation. Long noncoding RNAs (lncRNAs) play crucial roles in tumorigenesis. However, the potential interplay between lncRNA LINC01606 and ferroptosis in colon cancer remains elusive. Methods: The expression level of LNC01606 in colon cancer tissue was detected by quantitative real‐time polymerase chain reaction. The functional role of LNC01606 was investigated by gain‐ and loss‐of‐function assays both in vitro and in vivo. The LINC01606‐SCD1‐Wnt/β‐catenin‐TFE3 axis were screened and validated by DNA/RNA pull down, gas chromatography‐mass spectrometry, RNA immunoprecipitation and dual‐luciferase reporter. Results: The expression of lncRNA LINC01606 was frequently upregulated in human colon cancer and strongly associated with a poor prognosis. LINC01606 functioned as an oncogene and promotes colon cancer cell growth, invasion and stemness both in vitro and in vivo. Moreover, LINC01606 protected colon cancer cells from ferroptosis by decreasing the concentration of iron, lipid reactive oxygen species, mitochondrial superoxide and increasing mitochondrial membrane potential. Mechanistically, LINC01606 enhanced the expression of stearoyl‐CoA desaturase 1 (SCD1), serving as a competing endogenous RNA to modulate miR‐423‐5p expression, subsequently activating the canonical Wnt/β‐catenin signaling, and transcription factor binding to IGHM enhancer 3 (TFE3) increased LINC01606 transcription after recruitment to the promoter regions of LINC01606. Furthermore, we confirmed that upregulated LINC01606 and Wnt/β‐catenin formed a positive feedback regulatory loop, further inhibiting ferroptosis and enhancing stemness. Conclusions: LINC01606 functions as an oncogene to facilitate tumor cell stemness, proliferation and inhibit ferroptosis and is a promising therapeutic target for colon cancer. Abstract : LINC01606 functions as an oncogene to facilitate malignant phenotypes of colon cancer cells by enhancing tumour cell stemness and anti‐ferroptosis by Wnt/β‐catenin signalling; LINC01606 protects colon cancer cells from ferroptotic cell death by increasing the formation of monounsaturated fatty acids; LINC01606–Wnt/β‐catenin–TFE3 positive feedback regulatory loop signalling blocks ferroptosis and promotes stemness.